Pengembangan Aplikasi Penilaian Angka Kredit Dosen (Studi kasus: FMIPA Universitas Lampung) - Alifia Intan Andrean Nunyai; Tristiyanto Tristiyanto (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
According to Law Number 14 of 2005 on Teachers and Lecturers, lecturers are defined as professional educators and scholars whose primary responsibility is to transform, advance, and disseminate knowledge, technology, and the arts through education, research, and community service, often referred to as the Tri Dharma of Higher Education (Chapter 1, Article 1, paragraph 2). The assessment of lecturers' performance is deemed essential in the context of implementing the Tri Dharma of Higher Education to gauge the degree to which it is executed. In practice, lecturers are required to accrue credit points in line with the established standards specified in the operational guidelines for credit point assessment. Nevertheless, lecturers often encounter delays in the collection of these credit points, primarily due to the substantial amount of data used as assessment criteria and the manual creation of reports using Microsoft Excel. Consequently, this protracted process is responsible for the extensive time required for the preparation of Academic Qualification Credit Points (DUPAK) reports. To tackle this issue, the development of an Information System has been proposed to expedite and enhance the accuracy of data collection. The Information System is constructed using the prototype methodology, which encompasses three core phases: